Improving Transparency and Efficiency of Administrative and Organizational Governance Through Smart Digital Technology and Cloning Systems - Aspizain, Caniago; Syamsurizal, Syamsurizal; Masria, Masria; Rustanto, Agung Edi; Khabibjonovna , Kushieva Nodira; Wen, Goh Khang (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to improve the transparency and efficiency of administrative and organizational governance in mosque management through the development of Smart Mosque Digital Technology (SMDT) and a cloning system, enhancing financial administration and operational processes. Methodology: The study employs a mixed-methods approach, including literature review, interviews, surveys, and observational data collection. The SMDT application was developed using the Waterfall model of the System Development Life Cycle (SDLC). User satisfaction was measured through a questionnaire based on the End-User Computing Satisfaction (EUCS) model and analyzed using descriptive statistics with a sample of direct users from Nurul Jihad Mosque in Jakarta. Main Findings: The implementation of SMDT significantly improved transparency, accuracy, and efficiency in financial and administrative governance. User satisfaction levels were categorized as